In India... Exploring gladiolus for colour revolution - Dutt, Som (Indian Horticulture, 2019)
Floriculture sector is experiencing a rapid change world over with globalization and income generation. Consumption of gladiolus spikes in northern plains in India and coastal plains is rising day-by-day and this trend will continue to increase because of its demand in the market and improvement in purchasing power. A gladiolus spike has a potential to change economic scenario of poor farmers. The Editor (Indian Horticulture) interacted with Dr Manoj Nazir. Dr Nazir heads the National Gladiolus Trust. The excerpts of the interaction are furnished here.